Exponential Stability and Estimation of Solutions of Linear Differential Systems of Neutral Type with Constant Coefficients. (18th October 2010) - Baštinec Baštinec, J. J.; Diblík Diblík, J. J.; Khusainov Khusainov, D. Ya. D. Ya.; Ryvolová Ryvolová, A. A.
Abstract : This paper investigates the exponential-type stability of linear neutral delay differential systems with constant coefficients using Lyapunov-Krasovskii type functionals, more general than those reported in the literature. Delay-dependent conditions sufficient for the stability are formulated in terms of positivity of auxiliary matrices. The approach developed is used to characterize the decay of solutions (by inequalities for the norm of an arbitrary solution and its derivative) in the case of stability, as well as in a general case. Illustrative examples are shown and comparisons with known results are given.